An Analysis of Customer Perceptions of Service Quality in Islamic and Conventional Banks - Indri Yani Rangkuti; Salman Nasution (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2026)
This study compares customer perceptions of service quality between Islamic and conventional banks and examines whether significant differences exist in the services provided by the two systems. The research is motivated by differences in operational principles and service approaches that may shape customer evaluations. A comparative quantitative method was employed, with data collected through questionnaires distributed to purposively selected respondents. Prior to analysis, validity, reliability, normality, and homogeneity tests were conducted, followed by an independent sample t-test. The findings reveal significant differences in customer perceptions: conventional banks are perceived as superior in service speed, operational efficiency, and technological utilization, reflecting their stronger performance in delivering fast and accessible services. In contrast, Islamic banks demonstrate strengths in compliance with Sharia principles and customer care, highlighting their commitment to ethical practices and personalized relationships. The discussion emphasizes that efficiency and ease of access are primary determinants of perceived service quality. In conclusion, both banking models possess distinct advantages that can be leveraged to design service improvement strategies tailored to customer needs and expectations. These insights provide practical guidance for bank management in enhancing customer-oriented services while reinforcing the competitive strengths of each system.